Endotoxin in patients with terminal renal failure undergoing dialysis with re-processing dialyser - Markum, H M S; Suhardjono; Pohan, Herdiman T; Suhendro; Lydia, Aida; Inada, Katsuya (Acta medica Indonesiana, 2004)
to determine the level of endotoxin in the blood of patients with renal failure prior to and following hemodialysis using re-processing dialyser to know possibility of pyrogenic reactions in hemodialysis patients. this study subjects consisted of 10 patients with terminal renal failure undergoing regular hemodialysis. The collected samples were then sent in frozen condition for endotoxin examination in Japan. The normal level of endotoxin in the blood was < 9.8 pg/ml based on standard E.Coli E.0111 endotoxin quantitatively measured using Limulus Amoebocyte lysate test (the endospecy test). Statistical analysis was performed using paired student test. Ten patients with terminal renal failure who were undergoing hemodialysis were obtained, consisting of 1 female and 9 males. The mean age was 55.5 years (SD 6.74), the mean hemoglobin level 7.26 g/dl (SD 2.19), mean white blood cell (WBC) count 8660/mm(3) (SD 3064.2), and mean albumin level 3.59 g/l (SD 247). The etiologies of renal failure were as follows: glomerulonephritis (GN) 30%, Diabetic nephropathy (DN) 20%, hypertension (HT) 10%, interstitial nephritis (IN) 10%, obstruction/infection (01) 10%, unknown (U) 10%. The mean duration of hemodialysis was 97.9 month (SD 54.86). The mean endotoxin level prior to hemodialysis (ET pre-hemodialysis) was 5.4 pg/dl (SD 8). we conclude that terminal renal patients who undergoing re-processing hemodialysis did not have endotoxemia both prior to and following hemodialysis unless if they associated with infection, or other complications.